PENDAPAT DAN HARAPAN STAKEHOLDER TERHADAPTARIF DAN MUTU PELAYANAN KAMAR UTAMA DI RSUD KOTAYOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Background: In the middle of the year 2000 Yogyakarta Municipality Hospital opened new service to fulfill the demand of the middle and upper class by opening Very Important Person (VIP) room. This new product aims to improve the service quality and at the same time to receive financial sources for hospital. In the early phase, tariff had not been calculated according to unit cost, and only set to other hospitals in Yogyakarta Municipality. The research aims to discuss opinion and expectation of stakeholders about tariff and service quality of VIP room in Yogyakarta Municipality Hospital. Methods: The design of this study is observational. The subjects were: 1) external stakeholders, i.e. Local Parliament members, patients or their family members, 2) internal stakeholders, i.e. the specialists. Qualitative approach was used in this study using open-ended questionnaires, focus group discussion and in-depth interview. Results: Patient's opinion about the tariff was appropriate compared with the service quality. However, there were many complaints from community about tangible aspect of the hospital service. The increased of the tariff should be delayed. Specialist respondents said that there was a relation between service quality and tariff to affect the patient's satisfaction.They expected for the openness and fairness of their medical fee. Members of Local Parliament gave a autonomy of setting the VIP tariff. They expected that VIP room would provide commitments of the providers and improve patients' satisfaction. The revenue of the VIP room was not for cross subsidy. Conclusion: The VIP tariff is not set for a cross subsidy. The rational and fair tariff should increase commitment of the provider. The tariff should aim to meet high quality of service and professional standard.